DÉFORESTATION ET POLITIQUE DE REBOISEMENT DANS LES FORÊTS CLASSÉES : CAS DE LA FORÊT DE LA TÉNÉ (CENTREOUEST DE LA CÔTE D’IVOIRE) - Olivier, Eblin Marc; Célestin, Amani Yao (European Scientific Journal, ESJ, 2015)
Continuous deforestation is a phenomenon that manifests itself in the classified forest of Téné despite reforestation policy. From the study of the behavior of peasant populations and the analysis of the reforestation policy, it has been shown that the continuous deforestation of the classified forest of Téné reflects a reforestation policy both reductionist and incomplete. The flaws of this policy are observed in three points. The first deals with the incompleteness of the consolidation plan. The second lies in the maintenance of agricultural activities in the forest of Téné. The third point deals with the difficulties Téné surveillance by agents of the management unit. All these weaknesses explain the degradation suffered by the forest of Téné.